Inpatient costs, mortality and 30‐day re‐admission in patients with central‐line‐associated bloodstream infections. (6th November 2013) - Stevens, V.; Geiger, K.; Concannon, C.; Nelson, R. E.; Brown, J.; Dumyati, G.; Paul, M.
Abstract Previous work has suggested that central‐line‐associated bloodstream infection (CLABSI) is associated with increased costs and risk of mortality; however, no studies have looked at both total and variable costs, and information on outcomes outside of the intensive‐care unit (ICU) is sparse. The aim of this study was to determine the excess in‐hospital mortality and costs attributable to CLABSI in ICU and non‐ICU patients. We conducted a retrospective cohort and cost‐of‐illness study from the hospital perspective of 398 patients at a tertiary‐care academic medical centre from 1 January 2008 to 31 December 2010. All CLABSI patients and a simple random sample drawn from a list of all central lines inserted during the study period were included. Generalized linear models with log link and gamma distribution were used to model costs as a function of CLABSI and important covariates. Costs were adjusted to 2010 US dollars by use of the personal consumption expenditures for medical care index. We used multivariable logistic regression to identify independent predictors of in‐hospital mortality. Among both ICU and non‐ICU patients, adjusted variable costs for patients with CLABSI were c. 32 000 (2010 US dollars) higher on average than for patients without CLABSI. After we controlled for severity of illness and other healthcare‐associated infections, CLABSI was associated with a 2.27‐fold (95% CI 1.15–4.46) increased risk of mortality. Other healthcare‐associated infections were also significantly associated with greater costs and mortality. Overall, CLABSI was associated with significantly higher adjusted in‐hospital mortality and total and variable costs than those for patients without CLABSI.